Time to viral suppression is not related to achievement of SVR12 in HCV GT1‐infected patients treated with ombitasvir/paritaprevir/ritonavir and dasabuvir with or without ribavirin. Issue 4 (9th December 2016) - Alqahtani, S.; Ozaras, R.; Isakov, V.; Wyles, D.; Ferenci, P.; Feld, J. J.; Calinas, F.; Gschwantler, M.; Gane, E.; Crawford, D.; Jacobson, I. M.; Dumas, E. O.; et al.
Summary: High rates of sustained virologic response at post‐treatment week 12 (SVR12) were achieved in six phase 3 trials of ombitasvir (OBV, an NS5A inhibitor), paritaprevir (an NS3/4A protease inhibitor) co‐dosed with ritonavir (PTV/r) + dasabuvir (DSV, an NS5B RNA polymerase inhibitor) (ie, 3D regimen) with or without ribavirin (RBV) in adults with chronic genotype (GT) 1 hepatitis C virus (HCV) infection. We assessed whether time to first HCV RNA value below the lower limit of quantification in patients with and without cirrhosis was associated with achievement of SVR12. Data were analysed from GT1‐infected patients enrolled in six phase 3 studies of 3D ± RBV. Patients who experienced non‐virologic failure were excluded from analysis. HCV RNA was determined using the Roche COBAS TaqMan RT‐PCR assay (lower limit of quantification, LLOQ =25 IU/mL). SVR12 was analysed by week of first HCV RNA suppression, defined as HCV RNA <LLOQ. The analysis included a total of 2027 patients. Cumulative proportions of subjects with initial HCV RNA suppression <LLOQ at weeks 1, 2, 4 and 6 were 31%, 81%, 99% and 100%, respectively. SVR12 was achieved by 98%, 97%, 98% and 92% of patients with initial suppression at Weeks 1, 2, 4 and 6, respectively ( P =.42, trend test). Across six phase 3 trials of 3D ± RBV, most patients achieved viral suppression by week 2. Time to viral suppression was not associated with subsequent achievement of SVR12, suggesting that on‐treatment virologic monitoring may not be necessary with this regimen.